Le secteur résidentiel (bloc 3) de CANDIDE - Achour, Dominique (L'Actualité économique, 1976)
AbstractIn the first part, a synoptic review of the residential sectors in the balkanizing field of macro-econometric models is made à la M. Nerlove. The structural characteristics of most canadian and some american models are compared.Then, a detailed description of two versions (1.0 and 1.1) of the residential sector of CANDIDE is given and a non parametric evaluation presented. Some comparative parametric discussions are also introduced.The main weakness are stressed and some improvements are suggested.The residential sector of CANDIDE is generally adequately specified generating appropriate parameters and is relatively accurate in its medium term projections. Nevertheless, the model can be of little value as a policy instrument since it is not regionalized (provincialized) and does not include policy variables in a sufficiently explicit manner.